Altered expression of two Epstein-Barr virus early genes localized in BamHI-A in nonproducer Raji cells. - Zhang, C X (1988)
The Epstein-Barr virus-carrying lymphoblastoid cell line Raji has two major genomic deletions and is incapable of virus production. Two cDNA clones, c70 and c55, were constructed from early mRNA of P3HR-1 cells and localized, respectively, in BALF-2 and BARF-1 open reading frames where one of the major genomic deletion in Raji cells is situated. These were used to search the different early viral transcripts in producer P3HR-1 and nonproducer Raji lines. c70 and c55 hybridized with their corresponding mRNAs only in producer lines. Analysis with in vitro-synthesized RNA probes showed quite a different transcriptional profile in Raji cells than in P3HR-1 cells. In the P3HR-1 line, BALF-2 encodes a 3.4-kilobase (kb) mRNA during the early phase and a 3.3-kb mRNA during the late phase, and in the Raji line, the probe corresponding to BALF-2 hybridized with three mRNAs of 5.0, 3.1, and 2.4 kb; in P3HR-1 cells, BARF-1 encodes a group of 3'-conterminal transcripts (0.8, 1.2, 1.7, 2.7, 3.2, and 5.0 kb) during both the early and late stages; in Raji cells, however, 0.8-, 1.2-, and 1.7-kb mRNAs are absent, the only mRNAs transcribed being upstream of the deletion and of 5.0, 2.6, and 2.0 kb in size. In vivo and in vitro experiments demonstrated that the BALF-2 open reading frame encodes an early 135-kilodalton (kDa) protein which possesses DNA-binding ability and can be recognized by a herpes simplex virus ICP-8 antiserum. The BARF-1 open reading frame encodes in vitro a 26- to 33-kDa early protein recognized by anti-EA serum. The proteins of both two genes expressed in psi AM 22b cells were localized in nuclei. According to their properties, both proteins, particularly the BALF-2-encoded 135-kDa DNA-binding protein, could play a role in virus replication.